Mutant p53 tumor suppressor alleles release ras-induced cell cycle growth arrest. - Hicks, G G (1991)
Overexpression of an activated ras gene in the rat embryo fibroblast line REF52 results in growth arrest at either the G1/S or G2/M boundary of the cell cycle. Both the DNA tumor virus proteins simian virus 40 large T antigen and adenovirus 5 E1a are able to rescue ras induced lethality and cooperate with ras to fully transform REF52 cells. In this report, we present evidence that the wild-type activity of the tumor suppressor gene p53 is involved in the negative growth regulation of this model system. p53 genes encoding either a p53Val-135 or p53Pro-193 mutation express a highly stable p53 protein with a conformation-dependent loss of wild-type activity and the ability to eliminate any endogenous wild-type p53 activity in a dominant negative manner. In cotransfection assays, these mutant p53 genes are able to rescue REF52 cells from ras-induced growth arrest, resulting in established cell lines which express elevated levels of the ras oncoprotein and show morphological transformation. Full transformation, as assayed by tumor formation in nude mice, is found only in the p53Pro-193-plus-ras transfectants. These cells express higher levels of the ras protein than do the p53Val-135-plus-ras-transfected cells. Transfection of REF52 cells with ras alone or a full-length genomic wild-type p53 plus ras results in growth arrest and lethality. Therefore, the selective event for p53 inactivation or loss during tumor progression may be to overcome a cell cycle restriction induced by oncogene overexpression (ras). These results suggest that a normal function of p53 may be to mediate negative growth regulation in response to ras or other proliferative inducing signals.